Genotype by sequencing identifies natural selection as a driver of intraspecific divergence in Atlantic populations of the high dispersal marine invertebrate, Macoma petalum. Issue 19 (3rd September 2017) - Metivier, Stacy L.; Kim, Jin‐Hong; Addison, Jason A.
Abstract: Mitochondrial DNA analyses indicate that the Bay of Fundy population of the intertidal tellinid bivalve Macoma petalum is genetically divergent from coastal populations in the Gulf of Maine and Nova Scotia. To further examine the evolutionary forces driving this genetic break, we performed double digest genotype by sequencing (GBS) to survey the nuclear genome for evidence of both neutral and selective processes shaping this pattern. The resulting reads were mapped to a partial transcriptome of its sister species, M. balthica, to identify single nucleotide polymorphisms (SNPs) in protein‐coding genes. Population assignment tests, principle components analyses, analysis of molecular variance, and outlier tests all support differentiation between the Bay of Fundy genotype and the genotypes of the Gulf of Maine, Gulf of St. Lawrence, and Nova Scotia. Although both neutral and non‐neutral patterns of genetic subdivision were significant, genetic structure among the regions was nearly 20 times higher for loci putatively under selection, suggesting a strong role for natural selection as a driver of genetic diversity in this species. Genetic differences were the greatest between the Bay of Fundy and all other population samples, and some outlier proteins were involved in immunity‐related processes. Our results suggest that in combination with limited gene flow across the mouth of the Bay of Fundy, local adaptation is an important driver of intraspecific genetic variation in this marine species with high dispersal potential. Abstract : Recent studies of intertidal marine invertebrates have identified a phylogeographic break between the Bay of Fundy and Gulf Maine, which is driven (in part) by a strong gyre at the mouth of the Bay that limits alongshore dispersal. Here we take a genomics approach to show that while limited gene flow and genetic drift play a role in shaping patterns of diversity in the clam Macoma petalum, strong genetic structure at outlier loci suggests that natural selection is an important driver of interspecific divergence.